Regional variation in growth and survival responses to atmospheric nitrogen and sulfur deposition for 140 tree species across the United States - Dalton, Rebecca M.; Miller, Jesse N.; Greaver, Tara; Sabo, Robert D.; Austin, Kemen G.; Phelan, Jennifer N.; Thomas, R. Quinn; Clark, Christopher M. (Frontiers in Forests and Global Change, 2024)
We ask 1) are there significant regional differences in responses of tree growth and survival to atmospheric nitrogen (N) and sulfur (S) deposition across the conterminous U.S. and 2) do climate, soil pH, contemporary N and S deposition, mycorrhizal associations, and/or deciduousness correlate with these regional responses? Developing locally relevant tree growth and survival responses is essential for optimizing forest management plans and air pollution policy to protect ecosystem services and anticipate challenges to forests in a rapidly changing world. This primary research article falls within the scope of Frontiers in Forests and Global Change and the Forest Growth Section. Our work examines how atmospheric pollutants impact species' growth and survival across a broad spatial range. Additionally, we examine how the interactive effects of abiotic climate covariates, deciduousness, and mycorrhizal association influence tree species' growth and survival responses to air pollutant deposition.